Analysis of Factors Affecting Public Interest in Investing in the Capital Market - Anis Fajriyah; Siti Barokah (UIN Salatiga, 2021)
This study aims to determine the factors that influence public interest in investing in the capital market in the people of Semarang Regency, Indonesia. This study uses a quantitative approach. The research sample is the community or residents of Semarang as many as 62 people. The instrument used is a questionnaire. Data processing using SPSS program. The method of analysis with multiple linear regression model. In this research, the data analysis technique and variable measurement used validity test, reliability test, and classical assumption test. The results of the research test are that the variables of knowledge, income, and motivation have a significant positive effect on people's interest in investing in the capital market. While the risk variable has no significant effect on public interest in investing in the capital market.Keywords: Intention, knowledge, income, motivation, risk, investment